Manyampai Perwujudan Musik Sirompak di Nagari Taeh Baruah Kabupaten Lima Puluh Kota - Dicky Chandra; Alfalah Alfalah; Sriyanto Sriyanto (Institut Seni Indonesia Padangpanjang, 2023)
Sirompak is a traditional Minangkabau art originating from Taeh Baruah, Limapuluh Kota, West Sumatra. In the past, Sirompak was known as a magical ritual ceremony carried out by a sirompak handler whose aim was to avenge the heart of a woman who had insulted a man. The basirompak performance is a presentation of vocal music called dendang Minangkabau presentation of singing vocal music with the production of a wind instrument called saluang sirompak. This musical instrument is included in the classification of aerophone musical instruments (the main sound is produced by the vibration of blowing air). Traditional musical instruments accompany melodic vocals (dendang/mantras) by a singer (singer). The composition work